BIOACTIVE COMPOUNDS OF Moringa oleifera AS KRASG12C INHIBITORS IN COLORECTAL CANCER: IN SILICO STUDY - Marviella, Sephia Tiara; Zulqaida, Salma; Sulisetyawati, Theresia Indah Budhy; Ma'ruf, Anwar (Jurnal Kimia Riset, 2024)
KRAS is a GTPase enzyme that regulates cell growth and division. Mutations in KRAS can lead to its permanent activation, resulting in uncontrolled cell growth and cancer progression. Approximately 30–44% of colorectal cancer cases harbor KRAS mutations, with 1–3% involving the KRASG12C variant. Historically considered "undruggable," recent advancements, such as Sotorasib, have demonstrated the potential to target KRASG12C effectively, making it a promising focus for drug discovery. Moringa oleifera, a plant rich in phytochemicals, is a potential source of bioactive compounds with therapeutic applications. In this study, 218 compounds derived from M. oleifera were screened using molecular docking, targeting KRASG12C. Quercetin (3) exhibited the lowest binding affinity (-9.37 kcal/mol) and showed interactions with key residues, including GLN100A, VAL104A, LYS17A, and TYR97A, suggesting a binding mechanism similar to that of Sotorasib as native ligand. The physicochemical analysis further revealed high gastrointestinal absorption, good lipophilicity, and favorable bioavailability scores for Quercetin (3), supporting its potential as a drug candidate. These findings highlight the potential of M. oleifera compounds, particularly quercetin (3), as inhibitors of KRASG12C in colorectal cancer.